22nd International Conference on Human-Computer Interaction With Mobile Devices and Services 2020
DOI: 10.1145/3379503.3403552
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Performance and Usage of Input Methods for Soft Keyboard Hotkeys

Abstract: Touch-based devices, despite their mainstream availability, do not support a unified and efficient command selection mechanism, available on every platform and application. We advocate that hotkeys, conventionally used as a shortcut mechanism on desktop computers, could be generalized as a command selection mechanism for touch-based devices, even for keyboard-less applications. In this paper, we investigate the performance and usage of soft keyboard shortcuts or hotkeys (abbreviated SoftCuts) through two studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…What immediately strikes with these implementations is that there are neither consistent input methods to activate the command-selection mode nor consistent visual representation of the keys when the command-selection mode has been activated. A recent study demonstrated that the input method 'Once' (which relies on two sequential taps) is faster than holding (User Maintained) or swiping (Swipe) the modifier key across device configurations and mobility conditions [21]. However, this work only focuses on input methods and has yet to investigate the visual representation, discoverability or retention performance.…”
Section: Soft Keyboard Hotkeysmentioning
confidence: 99%
See 4 more Smart Citations
“…What immediately strikes with these implementations is that there are neither consistent input methods to activate the command-selection mode nor consistent visual representation of the keys when the command-selection mode has been activated. A recent study demonstrated that the input method 'Once' (which relies on two sequential taps) is faster than holding (User Maintained) or swiping (Swipe) the modifier key across device configurations and mobility conditions [21]. However, this work only focuses on input methods and has yet to investigate the visual representation, discoverability or retention performance.…”
Section: Soft Keyboard Hotkeysmentioning
confidence: 99%
“…While SoftCuts have been implemented on some commercial products, very little research was specifically conducted on them. To the best of our knowledge, the paper from Fennedy et al [21] remains the only work specifically focused on SoftCuts to this date. Their work, however, focuses on comparing the performance and adoption of different input methods under different size (phone or tablet) and handling (one-handed or two-handed) conditions.…”
Section: Motivation For Studying Softcutsmentioning
confidence: 99%
See 3 more Smart Citations